The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1212/wnl.54.5.1069
|View full text |Cite
|
Sign up to set email alerts
|

Decreased striatal dopamine transporter density in JNCL patients with parkinsonian symptoms

Abstract: The observed decrease in the striatal dopamine transporter density in JNCL offers a rational basis for a trial of dopaminergic drugs in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 20 publications
3
34
0
Order By: Relevance
“…To our knowledge, this is the first report showing quantitatively the amount of the mean gray matter loss be as high as 2.4% per year in JNCL patients during the adolescence, the time period when the clinical symptoms progresses fast [22]. The Cln3 mice model, in contrast to our JNCL patients, have not shown any brain volume loss in their adolescence or middle age [7].…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…To our knowledge, this is the first report showing quantitatively the amount of the mean gray matter loss be as high as 2.4% per year in JNCL patients during the adolescence, the time period when the clinical symptoms progresses fast [22]. The Cln3 mice model, in contrast to our JNCL patients, have not shown any brain volume loss in their adolescence or middle age [7].…”
Section: Discussionmentioning
confidence: 43%
“…One male patient was compound heterozygotes for the major mutation. All patients received antioxidants and epileptic drug treatment [22]. All patients were blind, had mental decline, epilepsy and parkinsonian symptoms, at least at the time of the last MRI examination.…”
Section: Methodsmentioning
confidence: 99%
“…Psychotic, affective, and schizophreniform features are managed with citalopram, risperidone, olanzapine, or quetiapine. 9 Reports of decreased D1 dopamine transporter density in JNCL by PET, 1, 80 along with similar findings in one of the Cln3 −/− mouse models, 95 suggest that JNCL patients may have a dysregulation of the dopamine system, offering a rationale for a trial of dopaminergic medications. 3 …”
Section: Treatmentmentioning
confidence: 90%
“…1, 2, 3, 83 Regardless of the specific anticonvulsant used, many JNCL patients’ seizures are well controlled.…”
Section: Treatmentmentioning
confidence: 99%
“…Imaging studies in JNCL patients have shown dysfunction in the striatum as measured by a reduction in dopamine transporter (DAT) levels and [ 18 F] fluorodopa uptake, an analog of dopamine (Ruottinen et al, 1997;Aberg et al, 2000). Once released into the synaptic cleft, dopamine activates either the D1 or D2 class of receptors.…”
Section: Introductionmentioning
confidence: 99%